What drives financial crises in emerging markets? - Tuomas Komulainen; Johanna Lukkarila (Bank of Finland, Institute for Economies in Transition (BOFIT), 2003)
The study examines the causes of financial crises in 31 emerging market countries during 1980 2001.It estimates a probit model using 23 macroeconomic and financial sector variables.Traditional variables such as unemployment and inflation, as well as several indicators of indebtedness such as private sector liabilities and the foreign liabilities of banks explain currency crises rather well, and it appears currency crises occur in tandem with banking crises.Indeed, in emerging market countries the vulnerability to crisis is exacerbated by situations involving large liabilities that permit sudden capital outflows.Increases in indebtedness followed the liberalization of capital flows and domestic financial sectors. Author
URN:NBN:fi:bof-201408072225
Keywords: F31; F32; F41; F47; 330; Currency crises; Banking crises; Emerging markets; Liberalization; Probit model